2016
DOI: 10.5664/jcsm.5416
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Related Scratching: A Distinct Parasomnia?

Abstract: Pruritus (itching) during the sleep period can present as a symptom of dermatological or systemic disease, or as a parasomnia. Sleep related scratching as a primary parasomnia, exclusively confined to sleep in the absence of coexisting dermatological disorders, has not been well described. This case series describes three such patients, and discusses potentially relevant pathophysiology that can underlie itching or pain. Such cases of sleep related scratching may merit nosologic classification apart from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Itch and associated scratching have been reported as disrupting sleep in psoriasis and other pruritic conditions, with scratching occurring throughout the sleep period . Evidence suggests that conditioned scratching activity can occur during sleep, with nocturnal scratching reported as a distinct parasomnia in a number of cases . Moreover, itch has strong links with mood, with depression amplifying itch perception .…”
Section: Discussionmentioning
confidence: 99%
“…Itch and associated scratching have been reported as disrupting sleep in psoriasis and other pruritic conditions, with scratching occurring throughout the sleep period . Evidence suggests that conditioned scratching activity can occur during sleep, with nocturnal scratching reported as a distinct parasomnia in a number of cases . Moreover, itch has strong links with mood, with depression amplifying itch perception .…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication of three cases suggested that nocturnal itch may occur in the absence of daytime pruritus and without the presence of a co-existent dermatologic or systemic condition [ 28 ]. Such findings suggest that nocturnal pruritus could constitute a parasomnia—abnormal behavior occurring during sleep.…”
Section: Stages Of Sleepmentioning
confidence: 99%
“…34,35 This may be due to biased attention towards symptoms and negative illness-related thoughts and worries, which further increase arousal and distress [36][37][38][39][40][41][42] and exacerbate sleep difficulties. Nocturnal itch and scratching were reported and may occur during sleep, 43 or during brief awakenings, thus interrupting sleep.…”
Section: Discussionmentioning
confidence: 99%